From GATT to the WTO : the secret story of the Uruguay Round : through 15 years of daily reports (Third World Network PenangMY, 1999)
Presents an important number of articles on the GATT-Uruguay Round and its follow-up, in order to make one understand more deeply this important process. Includes the whole text of the Uruguay Agreements.
Keywords: GATT